Using A Concrete-Representational Abstract (CRA) Approach In Learning Fractions Among Grade Five Iraqi Pupils - Ibrahim, Sahar Abbas (2017)
In the Iraqi education system, fractions is a topic introduced to primary school pupils since Grade Four until secondary school. However, pupils in Iraqi schools often face difficulties in learning fractions. Thus, the two main objectives of this study were to examine the effects of the CRA approach on Iraqi Grade Five pupils' proficiency and retention of proficiency in learning fractions; and also in their motivation and retention of motivation in learning fractions. In addition, it also investigated the pupils' perception, feedback of teacher and pupils about learning fractions using the CRA approach. This study adopted a one-group pretest-posttest-retention test research design where a class of 34 Grade Five pupils from an Iraqi school in Kuala Lumpur,